An objective comparison of two pulse oximetry sensors with different adhesive systems on healthy human volunteers based on biophysical assessments. Issue 1 (3rd November 2022) - Grove, Gary; Houser, Timothy; Dove, Jacob; Moody, Derek
Abstract: Background: Medical Adhesive Related Skin Injuries can arise from topically applied medical devices, especially in those with fragile skin, including the elderly and premature infants. The purpose of this study was to compare gentleness and reapplication of two pulse oximetry sensors (OxySoftN and MaxN, Medtronic, Boulder, CO). Materials and methods: Eighteen healthy subjects aged 65 years and older were enrolled in the gentleness trial, and 20 healthy subjects (18–69 years) were enrolled in the reapplication trial. For the gentleness trial, trans‐epidermal water loss (TEWL) measurements were made at five sites on each forearm at three time points (baseline [T0], 4‐h postinitial wear [T1], 4‐h postsecond wear [T2]). Total amount of protein adhered to each device was also determined. For the reapplication trial, a series of 180° peel tests were performed to observe the forces required to detach the sensor from the skin. Results: TEWL rates in the tail region were significantly greater with MaxN compared to OxySoftN at T1 ( p  < 0.05). Both were significantly greater than control ( p  < 0.05). Further, protein analysis revealed that the amount of protein removed was significantly less with OxySoftN compared to MaxN ( p  < < 0.0001). Differences in loss of adhesion of the tail region between the two sensors were demonstrated, with OxySoftN depreciating at a much slower rate compared with MaxN. Conclusion: The OxySoftN sensor appears to be gentle, even on fragile skin, based on reduced strain on the skin during removal. Further, it demonstrated the ability to withstand several reapplications without functional loss in adhesion.